Low order universal portfolios generated by special distributions - Ling, Hoong Chuan (2021)
Universal Portfolio is an investment strategy that enables inve their wealth by reallocating their invested wealth in the everyday stors to maximize portfolio. There is no stochastic model being assume d for the stock price in the universal portfolio. Five different companies are selected from Kuala Lumpur Stock Exchange (KLSE) to form three portfolios containing three different companies. This project's main objective is selected distributions to generate a loworder universal with two or three parameters . portfolio with As parameters of the distribution will affect the wealth generated by each distribution, therefore parameter sensitivity test was performed in this project to identify the best parameter for each distribution. To study the performance of a universal portfolio in the long term, we collected opening and closing stock prices for 2500 trading days. We generated the wealth for each 500, 1000, 1500, 2000, and 2500 trading days and compared each trading period's performance. Finally, we also study the universal portfolio's performance with a nondiversified and diversified portfolio. The result generated for the best constant rebalanced portfolio (BCRP) and constant rebalanced portfolio (CRP) are used as a benchmark to compare the performance of each distribution. The results obtained will be discussed in this project.